MOTO BELONG LOSJOYO PRODUCTION QUANTITY PREDICTION SYSTEM USING THE WEB BASED FUZZY TSUKAMOTO METHOD - Anjas, Anjas Ari Irawan; Tri Hastono; Fahmi Azkarizal Astrian (JTH: Journal of Technology and Health, 2024)
The Moto Belong Losjoyo factory currently still relies on estimates of production quantities without clear calculations and has not utilized computer technology to process production calculation data. Therefore, the use of the web-based Tsukamoto fuzzy method calculation system is expected to reduce losses due to mismatches in production quantities with market share. This research aims to help the Moto Belong Losjoyo factory in estimating daily production quantities in accordance with market needs. The test results using the Mean Absolute Percentage Error (MAPE) have shown that the system calculation accuracy level is 93.91%, with an error value of 6.09, confirming that the interpretation of the MAPE value shows a high level of accuracy.